2019
DOI: 10.4055/cios.2019.11.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Body Mass Index and Complications during the First 45 Days after Primary Total Hip and Knee Replacement: A Single-Center Study from South America

Abstract: Background The goal of this study was to evaluate the relationship between body mass index (BMI) and early complications of total hip replacement (THR) and total knee replacement (TKR). Methods This is a retrospective study of patients who underwent primary THR and TKR between January 2011 and December 2015. We included patients between 18 and 90 years of age with BMI less than 40 kg/m 2 with a minimal postoperative follow-up time of 45 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…However, more and more studies supported that BMI alone was not an independent risk factor for a higher complication rate and obesity could not lead to higher risk of complications . [29][30][31] In the long term, after the analysis of nationwide billing data in Germany, Jeschke et al 32 showed that elevated BMI could increase the risk of remotely 90 day complications and 1 year revision rates . Notably, above papers reached a consensus, which was that the complication risk will dramatically increase when the BMI was more than 40 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…However, more and more studies supported that BMI alone was not an independent risk factor for a higher complication rate and obesity could not lead to higher risk of complications . [29][30][31] In the long term, after the analysis of nationwide billing data in Germany, Jeschke et al 32 showed that elevated BMI could increase the risk of remotely 90 day complications and 1 year revision rates . Notably, above papers reached a consensus, which was that the complication risk will dramatically increase when the BMI was more than 40 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“… 2019 , Correa-Valderrama et al. 2019 ). For TKA, male patients have higher rates of revision surgery, mortality, hospital readmission, and wound infections compared with women, while female patients have increased risk of readmission, reoperation, and wound infection following THA (Singh et al.…”
Section: Methodsmentioning
confidence: 97%
“…In terms of in-hospital complications, examples of such poor outcomes include acute myocardial infarction, DVT or PE, surgical site infection, sepsis, hemorrhage, and mortality (Fang et al 2015). Similarly, patients with a BMI classification of ≥ 30 are more likely to experience prosthetic failure and postoperative infection following TKA and THA (Boyce et al 2019, Correa-Valderrama et al 2019. For TKA, male patients have higher rates of revision surgery, mortality, hospital readmission, and wound infections compared with women, while female patients have increased risk of readmission, reoperation, and wound infection following THA (Singh et al 2013, Patel et al 2020.…”
Section: Statisticsmentioning
confidence: 99%
“…Not only do these PFs normally require surgery, but the difficulty of the required surgeries is a challenge to orthopaedic surgeons 10 . Arthroplasty surgeons have made various efforts to prevent the PFs during the primary arthroplasty and evaluate the risks of PFs in the follow-up [11][12][13] . It has been suggested that age, gender, use of corticosteroids, poor bone quality, number of previous surgeries, stiff joints, neurological comorbidities, inflammatory arthropathy, and type of implants used in primary arthroplasties could increase the risk of PFs 2,4,6,[14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%